2017
DOI: 10.1177/1354816617724012
|View full text |Cite
|
Sign up to set email alerts
|

Income elasticity of demand for tourism at Fulufjället National Park

Abstract: National Parks are significant markers in the tourism attraction system and represent an important supply of recreation opportunities for the clients of the nature-based tourism industry. In this study, we analyze income elasticities among visitors from two major nationalities at Fulufjället National Park (FNP)—a cross-boundary park between Sweden and Norway—to see if this tourism product is a luxury or not. Modeling demand with a Tobit model, we find that visiting this National Park is close to a luxury, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Certainly, we can find destination-specific studies (e.g. Liu, 2016or Fredman & Wikström, 2018 but income elasticities at an intermediate, i.e. regional/provincial dimension are not common.…”
Section: Income Elasticity In Tourismmentioning
confidence: 86%
See 1 more Smart Citation
“…Certainly, we can find destination-specific studies (e.g. Liu, 2016or Fredman & Wikström, 2018 but income elasticities at an intermediate, i.e. regional/provincial dimension are not common.…”
Section: Income Elasticity In Tourismmentioning
confidence: 86%
“…Knowing the income elasticity of the origin markets allows local authorities to prepare and react to a foreseeable major drop in inbound flows in the event of an economic recession (Dougan, 2007;Lim, Min & McAleer, 2008;Saayman & Saayman, 2015;Smeral, 2009). The second application relates to destination marketing: the calculation of market-specific income elasticities aids in market segmentation (Álvarez-Díaz, González-Gómez & Otero-Giráldez, 2015;Lin, Liu & Song, 2015;Fredman & Wikström, 2018). It has been well-established that income elasticities change across origin countries (Jensen, 1998;Smeral, 2003;Smeral, 2014) as they are sensitive to income levels and business cycles.…”
Section: Income Elasticity In Tourismmentioning
confidence: 99%
“…Theoretical, methodological and empirical aspects of the demand for tourist services were dealt with, among others, by the following authors: Cortés-Jiménez and Blake (2011), Schiff and Becken (2011), Nelson, Dickey and Smith (2011), Wu, Li and Song (2012, Baležentis et al (2012), Konovalova andVidishcheva (2013), Fuleky, Zhao andBonham (2014), Gatt and Falzon (2014), Untong et al (2014Untong et al ( , 2015, Peng et al (2015), Martins, Gan and Ferreira-Lopes (2017), Dogru, Mariyono (2017), Sirakaya-Turk and Crouch (2017), Khoshnevis Yazdi and Khanalizadeh (2017), Falk and Lin (2018), Fredman and Wikström (2018) and Kumar and Kumar (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some scholars have empirically studied the impact of disasters on tourism. The authors [28][29][30][31] used time series and other methods to examine income, prices, exchange rates, fuel prices, inflation, and cultural proximity factors affecting tourism demand. Huang et al [32] studied the impact of the 1999 earthquake in Taiwan and found that the recovery period for the number of inbound tourists exceeded 11 months.…”
Section: Literature Reviewmentioning
confidence: 99%